2006
DOI: 10.1111/j.1528-1167.2006.00909.x
|View full text |Cite
|
Sign up to set email alerts
|

Hemispheric Surgery in Children with Refractory Epilepsy: Seizure Outcome, Complications, and Adaptive Function

Abstract: Summary:Purpose: To describe seizure control, complications, adaptive function and language skills following hemispheric surgery for epilepsy.Methods: Retrospective chart review of patients who underwent hemispheric surgery from July 1993 to June 2004 with a minimum follow-up of 12 months.Results: The study population comprised 24 children, median age at seizure onset six months and median age at surgery 41 months. Etiology included malformations of cortical development (7), infarction (7), Sturge-Weber Syndro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

16
122
0
14

Year Published

2010
2010
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 157 publications
(152 citation statements)
references
References 31 publications
16
122
0
14
Order By: Relevance
“…10 Hemispherectomy outcomes are usually good, with up to 100% of patients becoming seizure-free after the procedure. [3][4] Some authors have reported periods of seizure freedom as long as 17 years post-hemispherectomy in patients with SWS 11 . However these patients did not have recurrence of seizures for as long as they were followed.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…10 Hemispherectomy outcomes are usually good, with up to 100% of patients becoming seizure-free after the procedure. [3][4] Some authors have reported periods of seizure freedom as long as 17 years post-hemispherectomy in patients with SWS 11 . However these patients did not have recurrence of seizures for as long as they were followed.…”
Section: Discussionmentioning
confidence: 99%
“…Some form of hemispherectomy is usually performed for SWS-associated intractable epilepsy and most patients become seizure-free after surgery. [3][4][5] Another possible benefit of hemispherectomy is a better cognitive profile in patients that became seizure-free after such a procedure. However, very long follow-ups addressing seizure control and cognitive deficits in hemispherectomized patients are rare and they usually show good outcomes.…”
mentioning
confidence: 99%
“…5,18,19 Hemispherotomy certainly circumvents the problem of widespread epileptogenic networks in the setting of early vascular injury and is one of the most effective forms of epilepsy surgery across all etiologies, with seizure freedom rates as high as more than 90%. 1,35,36 Hemispheric disconnection/anatomical resection has been the mainstay of surgical therapy for large perinatal porencephalic cysts after MCA stroke. 18,34,35 In this subgroup, outstanding seizure control rates with Engel Class IA outcomes in almost 90% of patients have been reported.…”
Section: Discussionmentioning
confidence: 99%
“…Hemidisconnection provides a 63 to 85 percent seizure-freedom rate (1). Complication rates range from 24 to 41 percent, depending on the definition (12)(13)(14). Another potential benefit from surgery is that it frequently decreases medication burden and resulting side effects.…”
Section: Surgical Treatmentmentioning
confidence: 99%